A társadalmi kirekesztődés egyes kérdései az ezredforduló Magyarországán: Szegénység és kirekesztődés a rendszerváltás prizmáján - Szalai, Júlia (Szociológiai Szemle, 2024)
Part One of this study summarizes the general view of poverty since the political regime changed, and the practical consequences. The previous regime's denial and hiding of the poverty issue has had several effects. One is that poverty is considered foreign to the system, simply the fallout of economic crisis, and therefore transitional. The belief in its transitional nature has covered up the difference between mass impoverishment and lasting poverty, which always existed, is becoming increasingly serious, and can easily escalate into permanent exclusion. The need to dismantle an overcentralized state is a major reason why the poverty problem has not been understood. Public expenditure can be reduced with little resistance if only those 'who really need it' are assisted. This policy suggests that poverty is 'accidental' and individualized, and that the victims can be blamed. Another, more practical consequence has been the segregating effect of separate institutional poverty management. Institutional reforms have created a huge network of decentralized institutions, which have cut off poverty from other social problems. The social nature of poverty has thus been hidden under the guise of individualization as well as by transferring management to small communities. At the same time, these measures have anchored lines of demarcation between mainstream society and the poor. Part Two of the study focuses on the internal stratification of the poor. The result of impoverishment is that there is now a mass of income-poor people (retirees, low-income families, parents of young children), whose problems are 'only' ones of distribution. Since their bonds to mainstream society have not been fatally injured, their situation could be resolved with money and economic expansion. The other group of the poor are the long-standing, extremely poor. They are in a consolidated state of poverty from which escape is almost impossible. As individuals, people without families, or whose families are in a state of collapse, are in particularly dire situations. Others, who are unskilled and come from less competitive strata and have been driven off the increasingly limited labor market to lock themselves into the underground economy, are in a similarly ominous position. There are also two groups that are collectively poor. It is almost impossible to break out of tiny pockets of isolated settlements and of regions particularly depressed by mass unemployment. The other collective is made up of the victims of the dead-end of forced assimilation, primarily the Roma poor which make up 60-80 per cent of the Gypsy population.